Social Movement Donasi Makeup Tidak Terpakai Melalui Social Media - Fildzah Berliana; Fira Santika; J.A. Wempi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The Social Movement carried out by Makeup Wakeup is a form of real action to help reduce cosmetic waste, encouraging consumers to donate products that are no longer used but may still have some life left in them. This research uses an interpretative qualitative approach with data collection techniques using interview methods, literature study and document study. The research results show that Makeup Wakeup uses social media platforms, especially Instagram. Not only does it create awareness but also encourages people to get involved in the movement to donate unused cosmetics. The proceeds from collecting unused cosmetics are donated to the funeral beautician. The findings in the research are that wakeup makeup will collaborate with artists to increase attractiveness and create synergy between artists and environmental awareness.